Association of acne, hirsutism, androgen, anxiety, and depression on cognitive performance in polycystic ovary syndrome: A cross-sectional study - Saeideh Mehrabadi; Shahideh Jahanian Sadatmahalleh; Anoshirvan Kazemnejad; Ashraf Moini (Shahid Sadoughi University of Medical Sciences, 2020)
Background: While polycystic ovary syndrome (PCOS) is often associated with psychological distress, its most frequent clinical characteristics include acne, hirsutism and increased level of androgen hormones. Objective: To evaluate the level of depression and anxiety, hirsutism, acne, and level of androgen hormones in PCOS and control group and its association with cognitive function. Materials and Methods: This cross-sectional study was conducted on 53 women with PCOS and 50 healthy women as a control group. Data were collected using a questionnaire including the samples' demographic information, clinical features, clinical findings of hyperandrogenism, and the Beck Depression and Anxiety questionnaire. In addition, the acne and hirsutism levels of the subjects were evaluated using the global acne grading system and the Ferriman-Gallwey scoring system, respectively. The Montreal Cognitive Assessment (MoCA) is a screening test for cognitive impairment that covers major cognitive domains. Results: A significant difference was found between the two groups in the mean levels of acne, hirsutism, total testosterone, free androgen index, depression, and anxiety. However, some mean values of the MoCA were lower in the women of case group compared to the control group. Additionally, a significant difference was observed between the two groups in the domains of visual-spatial ability (p = 0.009), executive function (p = 0.05), attention (p = 0.03), and total MoCA scores (p = 0.002). Conclusion: The PCOS women demonstrated significantly lower performance on the tests of executive function, attention, and visual-spatial function than the healthy control women.